Morrill family papers - Morrill, Elijah, 1719-1767.; Morrill, Ezra, 1742-1797.
Ezra Morrill's account book (767-1784) of the estate of Elijah Morrill; a memorandum book (1760-1761) of blacksmith work; and Ezra Morrill's memorandum book of iron and iron work.
Blacksmith.
Collection material in English.
Keywords: Blacksmithing